Will Africa be part of the 'golden decade' of sustainable finance? Insights from GSSS bonds - Abel Gwaindepi; Krige Siebrits (Danish Institute for International Studies (DIIS), 2023)
The inadequacy of public financing mechanisms for sustainable development and climate action is increasingly evident. The focus has shifted towards private sector financing mechanisms to bridge these financing gaps. This study analyses the Green, Social, Sustainability and Sustainability-linked (GSSS) bonds, considered as the quintessential private sector financing instruments and projected to lead the 2020s' sustainable finance 'golden decade'. While evidence shows their explosive growth in developed markets, their impact on unlocking private-sector finance for Africa remains underexplored. We examine general trends in Africa's GSSS markets relative to other regions and gather data on 54 individual GSSS bonds issued, analysing tenors, issuer types, deal sizes, coupon rates and use of proceeds. Our findings reveal that African GSSS bond issuances account for less than 1% of the global volume and value. The realised amounts remain minuscule compared to the financing needs of USD 213.4 billion annually for climate action and USD 1.3 trillion for sustainable development. The GSSS bond market in Africa is unevenly distributed, with South Africa dominating over half its market value. Among GSSS categories, green-labelled bonds are the most popular, and the energy sector attracts the largest share of the limited funds. Financial corporations, especially commercial banks, primarily drive the GSSS bond markets, although through small deals that rarely exceed the current benchmark deal size of USD 500 million necessary for large-scale and impactful projects. We argue that since the quintessential private sector instruments show these disappointing results for Africa, the current actions and efforts to escort private sector finance need to be increased exponentially. It thus remains crucial not to overlook both private and public alternative financing methods. Currently, there seems to be no feasible framework to ensure the success of GSSS instruments at the required scale. Their suitability for Africa needs constant scrutiny compared to other private mechanisms such as blended finance. Ultimately, the need to innovate in the field of financial instruments cannot supersede the necessary groundwork, especially on project pipelines which involve costs at pre-feasibility stages, but will likely determine the best financing instruments for African countries.
Keywords: 330; Africa; GSSS bonds; Green; Social; Sustainabilit and Sustainability-linked (GSSS) bonds; "golden decade"; sustainable finance